Finding A Seat at the Table Together: Recommendations for Improving Collaboration between Social Work and Bioethics. (26th July 2014) - Brazg, Tracy; Dotolo, Danae; Blacksher, Erika
Abstract Social work and bioethics are fields deeply committed to cross‐disciplinary collaboration to do their respective work. While scholars and practitioners from both fields share a commitment to social justice and to respecting the dignity, integrity and the worth of all persons, the overlap between the fields, including shared values, has received little attention. The purpose of this article is to describe the ways in which greater collaboration between the two fields can broaden their scope, enrich their scholarship, and better ground their practice. We describe the potential for realizing such benefits in two areas – health care ethics consultation and social inequalities in health – arguing that the fields both complement and challenge one another, making them ideal partners for the interdisciplinary inquiry and problem‐solving so often called for today in health and health care.